2014
DOI: 10.4321/s1139-76322014000500004
|View full text |Cite
|
Sign up to set email alerts
|

Influencia del sexo y el tipo de escuela sobre los índices de sobrepeso y obesidad

Abstract: Influencia del sexo y el tipo de escuela sobre los índices de sobrepeso y obesidad Introducción: el sobrepeso y la obesidad infantiles han pasado a ser, en las últimas décadas, una epidemia que afecta especialmente a los países desarrollados. Cada vez son más las repercusiones negativas sobre la salud que tienen relación con la obesidad infantil. El objetivo de este estudio fue determinar las prevalencias de sobrepeso y obesidad de una ciudad del norte de España, así como identificar los factores que influyen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
2
2
0
2
Order By: Relevance
“…Thus, we observed that being a girl or boy did not predict the likelihood of having excess weight/obesity, a finding that is consistent with some previous studies conducted [42,43]. However, contrary to our results, some other studies either reported differences in obesity prevalence between the sexes [17,21,44] or found girls to be at increased risk for childhood obesity [39]. In the case of %BF, we found a greater number of girls with higher adiposity than boys.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Thus, we observed that being a girl or boy did not predict the likelihood of having excess weight/obesity, a finding that is consistent with some previous studies conducted [42,43]. However, contrary to our results, some other studies either reported differences in obesity prevalence between the sexes [17,21,44] or found girls to be at increased risk for childhood obesity [39]. In the case of %BF, we found a greater number of girls with higher adiposity than boys.…”
Section: Discussionsupporting
confidence: 83%
“…For these reasons, evaluation accompanied by other body composition variables is highly recommended, such as waist-to-height ratio (WHtR), waist circumference (WC), or skinfolds in order to effectively determine the risk in participants [15]. Following this line, some studies have been conducted in order to assess the association between weight status (assessed by BMI) and socio-demographic factors, such as sex [16], type of schooling [17], area of residence [18], immigrant status [19], or per capita income [20]. For example, children from public schools have been associated with a higher prevalence of overweight or obesity [17], as well as children belonging to an immigrant family [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para los proyectos de promoción de vida saludable se debería de tener en cuenta tanto lo anterior como lo que otros estudios aportan ya que apoyan la garantía de apostar por esta clase de motivación (Moreno, Cervelló y Borges, 2010). Arriscado, Muros, Zabala y Dalmau (2014) concluyen que invertir para el fomento de estilos de vida saludables es el camino adecuado para ahorrar tratamientos de enfermedades y patologías que provengan de la falta de actividad física y de un mal planteamiento dietético. educación para la salud en España.…”
Section: Palabras Claveunclassified
“…Durante la etapa escolar es relevante establecer hábitos de alimentación saludables porque es en la infancia temprana donde se adquieren (Brug, Tak, te Velde, Bere y de Bourdeaudhuij, 2008) que pueden continuar en la etapa adulta de una persona (Craigie, Lake, Kelly, Adamson y Mathers, 2011). Arriscado et al (2014) estudiaron la adherencia a la DM en relación al tiempo que se pasa frente a la pantalla y las horas de sueño por la noche en días lectivos. Se concluyó que los escolares que tenían hábitos de alimentación poco saludables presentaban al mismo tiempo sedentarismo.…”
Section: Palabras Claveunclassified